The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1111/j.1467-8306.1967.tb00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Certain Aspects of the Expansion of Quantitative Methodology in American Geography

Abstract: Since the nineteenth century, American geographers have applied mathematical concepts to geographic research, and they have increased the level of mathematical sophistication associated with their research. To some extent geographers have traditionally been interested in developing methods of quantitative geographic analysis; however, it was not until the turn of the twentieth century that there was concentrated effort to develop special programs of quantitative methods training and to expand the scope of quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…(Golledge, 2009: 481) The first of these three reports reprised human geography's theoretical and quantitative revolutions' origins. By the 1970s quantification had penetrated deeply into both UK undergraduate and North American postgraduate programmes (Lavalle et al, 1967;Robson, 1970;Whitehand, 1970Whitehand, , 1971. But the revolution was never completed; as that 'new geography' approached dominance it was challenged by several alternative perspectives (Johnston and Sidaway, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(Golledge, 2009: 481) The first of these three reports reprised human geography's theoretical and quantitative revolutions' origins. By the 1970s quantification had penetrated deeply into both UK undergraduate and North American postgraduate programmes (Lavalle et al, 1967;Robson, 1970;Whitehand, 1970Whitehand, , 1971. But the revolution was never completed; as that 'new geography' approached dominance it was challenged by several alternative perspectives (Johnston and Sidaway, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative-theoretical work never achieved disciplinary dominance, however, even in areas such as urban geography (as illustrated by Wheeler, 2002), partly because of resistance – not only from some traditional ‘regional geographers’ but also in historical and cultural geography too, plus some resistant economic and social geographers. The quantifiers had established a strong position in most North American geography departments, as exemplified by compulsory courses in statistics there; LaValle et al (1967) reported that courses in quantitative methods were offered in 78 per cent of graduate schools in 1965, compared to only 3 per cent a decade earlier. But their putative revolution had failed; no sooner had they established this strong bridgehead than other revolutions were being fomented, offering alternative approaches to the discipline with very different epistemological and ontological foundations, let alone methodological protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The quantifiers had established a strong position in most North American geography departments, as exemplified by compulsory courses in statistics there; LaValle et al (1967) reported that courses in quantitative methods were offered in 78 per cent of graduate schools in 1965, compared to only 3 per cent a decade earlier. But their putative revolution had failed; no sooner had they established this strong bridgehead than other revolutions were being fomented, offering alternative approaches to the discipline with very different epistemological and ontological foundations, let alone methodological protocols.…”
mentioning
confidence: 99%
“…In fact geography has recently experienced something of a reorientation in its research practice (Gould, 1969), which has come to be known as the "quantitative revolution" (Burton, 1963). Thus whereas in 1955 a geographical article incorporating a correlation coefficient was a rarity, by 1965 such studies were commonplace (Lavalle, McConnell and Brown, 1967). This revolution in practice has several implications.…”
mentioning
confidence: 99%